How to Assess Ictal Consciousness? - Mirja Johanson; Katja Valli; Antti Revonsuo (Behavioural Neurology)
Despite the complexity and methodological difficulties in defining the concept of consciousness, it is a central concept in epileptology, and should thus be tractable for scientific analysis. In the present article, a two-dimensional model consisting of concepts related to the level and the contents of consciousness will be presented. This model has been found to be well suited for the description of seizure-induced alterations of consciousness, and is supported both by findings from neuroimaging and electrophysiological studies as well as from phenomenological studies. Further, we will review both traditional introspective methods as well as methods that have recently been developed or utilized in epilepsy research, summarize the main findings concerning first person experiences during epileptic seizures acquired with some of these methods, and discuss their strengths and weaknesses.